2010
DOI: 10.1007/s11274-010-0556-7
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Vibrio cholerae non-O1 in three wastewater treatment plants in Agadir (Morocco)

Abstract: A total of 21 isolates of Vibrio cholerae non-O1 strains were isolated from three wastewater treatment plants in Agadir, Morocco. The isolates were analyzed by biochemical analysis, antibiogram, pulsed-field gel electrophoresis and the MALDI-TOF patterns of their protein masses were compared. Over 67% of isolates were susceptible to antimicrobial agents tested and 14% proved resistant to both trimethoprim-sulfamethoxazole and nalidixic acid. Typing by pulsed-field gel electrophoresis with NotI digestion reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…; Eddabra et al . ). Another disadvantage of molecular methods is a weaker reproducibility because of variations in band intensity and the presence of some minor bands, requiring the use of other PCR methods for typing V. parahaemolyticus (Wong and Chih‐Hsueh ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…; Eddabra et al . ). Another disadvantage of molecular methods is a weaker reproducibility because of variations in band intensity and the presence of some minor bands, requiring the use of other PCR methods for typing V. parahaemolyticus (Wong and Chih‐Hsueh ).…”
Section: Resultsmentioning
confidence: 97%
“…An increase in the frequency of V. parahaemolyticus associated-infections has heightened the need for a rapid and reliable method for the identification of V. parahaemolyticus strains (Daniels et al 2000;Nair et al 2007). The major advantages of using MALDI-TOF/ MS-based protein mass spectral fingerprinting for the identification of micro-organisms as well as for their differentiation at the subspecies level are the ease to treat large series, the analytic speed, with relatively simple sample preparation techniques, the potential for the identification of mixed cultures and a rapid identification of candidate biomarkers, even when minimal genetic data are available (Eddabra et al 2011). The accuracy and speed of data acquisition make MALDI-TOF MS a powerful tool especially suited for environmental monitoring and detection of biological hazards in food processing plants and in the hospital.…”
Section: Vibrio Parahaemolyticus Is a Significant Pathogen In Marine mentioning
confidence: 99%
See 1 more Smart Citation
“…The target genes (Table 1) specific for the identification of these pathotypes were not detected in the tested isolates. With the exception of V. cholera which could not be tested the tested strains are not ubiquitous to the natural fresh or salt aquatic environment as are the V. cholera [11]. V. fluvialis, V. parahaemolyticus and V. vulnificus are reported as the most frequently encountered pathogenic Vibrios in marine environments, coastal, estuaries and brackish waters as well as seafood, which is considered a natural habitat for this strains of Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…The aquatic environment have been identified to be a medium of transmission of this organism through which the isolation of the organism has been found in seafood [7,9,10]. The isolation of the microorganism from raw sewerage as well as the final treated effluent showed that wastewater treatment plants do not remove or inactivate all pathogenic microorganisms [11,12] and hence Wastewater has been implicated in the distribution of Vibrio in the environment and surface water [13,14]. Study have shown the presence of high level antibiotic resistance Vibrio cholera e in the final effluent of stabilization pond revealing the imminent danger of poorly treated effluent [15].…”
Section: Introductionmentioning
confidence: 99%